Comparison of Clean Energy Trading Method in Microgrid by using Blockchain Technique - Ahmed, Manzar; Yasir Ali, Agha; Rehan, Muhammad; Ahmed, Afsar; Amin, Uzma; Ahmed, Mishaal (2022)
The old conventional energy distriution system cannot fulfill the demand of the prosumers in providing secure energy trading and with minimum losses in energy transmission. Because it is centralized system and user has no freedom to trade energy without involving the third party. In conventional grid there are lot of issues such as controlling the losses and forecasting the demand and reliability. One major issue is theft of electricity and losses. The new blockchain system has potential to provide secure energy trading in network without involvement of third party. The combination of blockchain and Microgrid has all features to resolve the issues related to the current grid such as controlling power, Forecasting the demand and reliability. In this paper the combination of Microgrid and blockchain for trading energy will be analyzed and energy trading method in P2P Network based will be investigated to find best method for trading enegy in network. For the simulation the matlab tool will be used.